2021
DOI: 10.1186/s12882-021-02247-8
|View full text |Cite
|
Sign up to set email alerts
|

Anemia among Chinese patients with chronic kidney disease and its association with quality of life - results from the Chinese cohort study of chronic kidney disease (C-STRIDE)

Abstract: Background Anemia is one of the common complications in patients with chronic kidney disease (CKD). However, there is no systematic investigation on the prevalence of anemia in CKD patients and its relationship with the quality of life in China. Methods The data for this study comes from baseline data from the Chinese Chronic Kidney Disease Cohort Study (C-STRIDE), which recruited predialysis CKD patients in China. The kidney disease quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(6 reference statements)
2
2
0
Order By: Relevance
“…The CKD Outcomes and Practice Patterns Study, 8 a prospective cohort of 2465 patients with stage 3–5 CKD, found that anemia was associated with lower (worse) overall health-related quality of life and with the emotional and physical domains of health-related quality of life, as well as with physical inactivity. Similar findings were obtained in the CKD RenalSoft Informatics Observational Study, 31 a prospective cohort of 1186 patients with stage 3–5 CKD, that assessed physical functioning using the Kidney Disease Quality of Life Short Form Questionnaire and in the Chinese Cohort Study of CKD, 32 a multicenter prospective cohort of 2921 patients with CKD. Furthermore, a large real-world cross-sectional multicounty survey of 5276 patients with CKD 33 found that lower hemoglobin levels worsened the effect of CKD on health-related quality of life.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The CKD Outcomes and Practice Patterns Study, 8 a prospective cohort of 2465 patients with stage 3–5 CKD, found that anemia was associated with lower (worse) overall health-related quality of life and with the emotional and physical domains of health-related quality of life, as well as with physical inactivity. Similar findings were obtained in the CKD RenalSoft Informatics Observational Study, 31 a prospective cohort of 1186 patients with stage 3–5 CKD, that assessed physical functioning using the Kidney Disease Quality of Life Short Form Questionnaire and in the Chinese Cohort Study of CKD, 32 a multicenter prospective cohort of 2921 patients with CKD. Furthermore, a large real-world cross-sectional multicounty survey of 5276 patients with CKD 33 found that lower hemoglobin levels worsened the effect of CKD on health-related quality of life.…”
Section: Discussionsupporting
confidence: 74%
“…The few studies that have assessed the association between anemia and functional outcomes have been restricted to nondialysis patients with CKD stages 3 or greater 8 , 31 33 or restricted to hemodialysis patients. 34 As expected from studies in CKD populations, in all these studies, the mean hemoglobin levels were lower, and the proportion of participants with moderate-to-severe anemia (hemoglobin <10 g/dl) was higher than in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…A clear and consistent association between anaemia and poorer HRQoL has been repeatedly reported, with more pronounced benefits of higher Hb levels after treatment with ESAs in younger and ND-CKD patients [119][120][121][122][123]. However, improvement in HRQoL strongly attenuates for Hb > 12 g/dL after ESA [124,125], thus confirming that complete correction of anaemia by ESA provides small advantages for selected domains of HRQoL [15,126,127].…”
Section: Quality Of Lifesupporting
confidence: 57%
“…17,18 The stages of CKD were also associated with a high prevalence of anemia. 19,20 This accounts for stages 3, 4, and 5. Patients with higher stages of CKD were found to have severe anemia defined by hemoglobin below 8 g/dl.…”
Section: Resultsmentioning
confidence: 99%